New Zealand Jazz Concerts, the Use and Abuse of Grand Pianos, and One Cartoonist's Response. Issue 1 (23rd August 2016) - Ward, Aleisha
Abstract : Political, social, and cultural controversies are the main fodder of staff cartoonists at newspapers. From the serious to the silly, newspaper cartoonists are expected to comment on whatever happens to be in the news cycle on any day. This commentary creates both ephemera and historical evidence of events and their effects on society. This article investigates an incident at a jazz concert in Auckland in 1952 at which the musicians were charged with abusing the new Steinway grand piano and the following controversy about the jazz musicians' use of town hall facilities. From this incident New Zealand Herald cartoonist Gordon Minhinnick responded with a cartoon and a comic strip about the debate. By examining Minhinnick's contributions via the lens of cultural history we can apprehend the shape of this dispute (politically and culturally), how it impacted Auckland society, and also gain a sense about how jazz was perceived by society at large at that time. We can also see how Minhinnick used the debate to illustrate other important political issues facing Auckland at the time.